1998
DOI: 10.1590/s1516-89131998000400002
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of artificial substrata by teredinid larvae released from a previously infested focus at Ilha Grande Bay, RJ

Abstract: The colonization pattern of wooden panels by teredinid larvae released from a previously infested focus was investigated. Panels were placed at different distances (1, 10, 20m)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
3
2
2
Order By: Relevance
“…Both species have been recognized as dominant in Ilha Grande Bay OMENA et al, 1990), with the dominance of L. floridanus. However, in VAROTTO; BARRETO (1998) and in two estuarine regions in the present study (Barra Grande and Bracuy rivers), the dominant species is Teredo furcifera and BARRETO et al (1993) found Bankia gouldi to be the dominant species. The latter study was conducted at the same site as that of VAROTTO and BARRETO (1998), but our study sites did not include this exact location.…”
contrasting
confidence: 54%
See 3 more Smart Citations
“…Both species have been recognized as dominant in Ilha Grande Bay OMENA et al, 1990), with the dominance of L. floridanus. However, in VAROTTO; BARRETO (1998) and in two estuarine regions in the present study (Barra Grande and Bracuy rivers), the dominant species is Teredo furcifera and BARRETO et al (1993) found Bankia gouldi to be the dominant species. The latter study was conducted at the same site as that of VAROTTO and BARRETO (1998), but our study sites did not include this exact location.…”
contrasting
confidence: 54%
“…However, in VAROTTO; BARRETO (1998) and in two estuarine regions in the present study (Barra Grande and Bracuy rivers), the dominant species is Teredo furcifera and BARRETO et al (1993) found Bankia gouldi to be the dominant species. The latter study was conducted at the same site as that of VAROTTO and BARRETO (1998), but our study sites did not include this exact location. This suggests that the high environmental heterogeneity of Ilha Grande Bay (CREED et al, 2007) implies differences in the dominant species according to location.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…Os moluscos xilófagos são de grande interesse para estudos devido à algumas características como a sua capacidade de degradar materiais lignocelulósicos, a importante função no ciclo de carbono marinho (DISTEL et al, 2011). Apesar desta influência ecológica fundamental para a ciclagem de nutrientes no ambiente marinho, estão constantemente relacionados a prejuízos financeiros devido aos danos causados em estruturas de madeira (VAROTTO; BARRETO, 1998;BORGES, 2014).…”
Section: Introductionunclassified